ROBLEMATIKA SYAFAQ DAN FAJAR : STUDI ANALISIS WAKTU ISYA DAN SUBUH - Ria, Nurhijriah; Chotban , Sippah (UIN ALAUDDIN MAKASSAR, 2022)
The problem of the time of syafaq and dawn (Isha and Fajr time), which has become a very urgent and fundamental determination of prayer times in the implementation of prayer and cannot be separated from the problem between fiqh and astronomical perspectives. Fajr sadik which is a benchmark as a marker of the beginning of the time for the dawn prayer, which must be faced with the dawn of kazib. Meanwhile, a similar study should be carried out on syafaq considering that both are similar, only that there is a difference between the time of occurrence. So that it can cause confusion to the general public who do not understand the problem of science. In this case because it is based on the difference in the height of the sun. In its application, some use the criteria of -18 degrees to -13 degrees as the value of the height of the Sun, but there are also some who use -19 degrees and -20 degrees. In this case, it can be caused by several factors, namely natural factors, altitude, weather conditions, air and light pollution, as well as several factors that arise from the tools and observations. Of the many factors, the biggest influence on the difference in the criteria for the height of the sun is the altitude.